Pendidikan Multikulturalisme Abad ke-21: Integrasi Nilai Kesadaran Sejarah dan Hak Asasi Manusia - Ruslan, Ahmad; Naredi, Hari; Muhtarom, Herdin (SAP (Susunan Artikel Pendidikan), 2024)
This research is urgent regarding multicultural education in the 21st century with a focus on integrating the values of historical awareness and human rights, including harmony in multicultural societies. The study employs a mixed methods approach, with data collection through surveys conducted on January 24, 2022. The aim of this research is to understand Multicultural Education in the 21st Century: Integrating the Values of Historical Awareness and Human Rights. The findings of this research indicate that the incorporation of historical values within the context of human rights provides a profound understanding of past events and their impact on current social conditions. Understanding history is crucial in preventing the repetition of mistakes related to human rights violations and in valuing human dignity comprehensively. The ability to empathize with history also plays a significant role in building reconciliation and peace.